Design of AlN-based micro-channel heat sink in direct bond copper for power electronics packaging - Yin, Shan (2013)
A single-phase, laminar flow, rectangular, and AlN-based micro-channel heat sink (MCHS) with water coolant has been designed and optimized for power electronics packaging. By fabricating micro-channels in the AlN-layer of direct bond copper, the heat conduction path is minimized and high cooling performance of micro-channels is utilized. The scaling effects, including temperature-dependent fluid properties, entrance effect, viscous dissipation and conjugate heat transfer, are considered. Comparison between CFD simulation by ANSYS Fluent and well-established analytical correlations is carried out and importance of entrance effect is emphasized. For the optimal geometry, the total thermal resistance of the AlN-based MCHS is 0.128 K/W at a pressure drop of 66.6 kPa. The conventional packaging structures, in which the Cu-based MCHS is bonded to the direct bond copper by solder or thermal interface material, are investigated to compare with the proposed structure. The proposed structure shows a reduction in thermal resistance by 15% and 80% respectively.